Implementation of Trademark Registration in Pekanbaru - Yufrizal, Yufrizal; Syafrinaldi, Syafrinaldi; Thalib, Abdul; Susanti, Heni (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The use of Intellectual Property Rights, especially product brand registration for Micro, Small and Medium Enterprises, has not been running optimally in Indonesia, and especially in the city of Pekanbaru, due to the lack of understanding of home industry entrepreneurs about brands and registration procedures, lack of technical guidance and programmatic socialization from the Regional Government. Purpose. This study aims to analyze the low implementation of product trademark registration for Micro, Small and Medium Enterprises and to analyze the role of the local government of Pekanbaru city in the implementation of product trademark registration for Micro, Small and Medium Enterprises in improving trade business. Method. The approach used in this study is a normative juridical approach and an empirical juridical approach to obtain correct and objective research results. Results. Based on the results of the study, it is known that the implementation of product trademark registration for Micro, Small and Medium Enterprises in Pekanbaru city has not been running as expected, as evidenced in 2022, out of 25,074 trademarks circulating in the market, only 8 (eight) have implemented their trademark registration. Conclusion. Furthermore, it is known that the role of local government in the implementation of trademark registration for Micro, Small and Medium Enterprises in Pekanbaru city is not running as expected, because the local government of Pekanbaru city has not given maximum attention to Micro, Small and Medium Enterprises so that they do not develop and make updates in innovating in accordance with science and technology and community needs.